Long-term orientation in family and non-family firms: A Bayesian analysis - Jörn Hendrich Block; Andreas Thams (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2007)
A stronger long-term orientation is considered a competitive advantage of family firms relative to non-family firms. In this study, we use panel data of U.S. firms and analyze this proposition. Our findings are surprising. Only in when the family is involved in the management of the firm is the firm found to invest more in long-term projects relative to a non-family firm. We also find that investment in long-term projects in family firms is determined less by cash flow variations than for non-family firms. Managerial implications of our findings are discussed. Our hypotheses are tested using Bayesian methods.
Keywords: C11; D21; G31; G32; L20; M31; O32; 330; Family Firm; Long-term Orientation; Myopia; Bayesian Analysis; Agency Theory; Stewardship Theory; Investment Policy; Betriebliche Investitionspolitik; Dauer; Familienunternehmen; USA